Efficacy and safety of a novel 450 nm blue diode laser versus plasmakinetic electrocautery for the transurethral resection of non-muscle invasive bladder cancer: The protocol and result of a multicenter randomized controlled trial - Wu, Kaijie; Jiang, Dali; Zhang, Lianhua; Jiang, Shuai; Lin, Tianhai; Luo, Yi; Fan, Jinhai; Yang, Tao; Chen, Haige; Zhang, Peng; Wang, Xinghuan; Wei, Qiang; et al. (Frontiers in Oncology, 2023)
Objectives: To be the first to apply a novel 450 nm blue diode laser in transurethral resection of bladder tumour (TURBt) to treat patients with non-muscle invasive bladder cancer (NMIBC) and evaluate its efficacy and safety during the preoperative period compared to the conventional plasmakinetic electrocautery. Materials and Methods: Randomized controlled trial (RCT) in five medical centres was designed as a non-inferiority study and conducted from October 2018 to December 2019. Patients with NMIBC were randomized to the blue laser or plasmakinetic electrocautery group for TURBt. As the first study to evaluate this novel blue laser device, the primary outcome was the effective resection rate of bladder tumours, including effective dissection and haemostasis. The secondary outcomes were the perioperative records, including surgical time, postoperative indwelling catheter time, hospital stay length, blood loss, reoperation rate, wound healing and adverse events. Results: A total of 174 patients were randomized to either the blue laser group (85 patients) or plasmakinetic electrocautery group (89 patients). There was no statistical significance in the clinical features of bladder tumours, including tumour site, number and maximum lesion size. Both the blue laser and plasmakinetic electrocautery could effectively dissect all visible bladder tumours. The surgical time for patients in the blue laser group was longer (p=0.001), but their blood loss was less than that of patients in the control group (p=0.003). There were no differences in the postoperative indwelling catheter time, hospital stay length, reoperation rate or other adverse events. However, the patients undergoing TURBt with the blue laser showed a faster wound healing at 3 months after operation. Conclusion: The novel blue laser could be effectively and safely used for TURBt in patients with NMIBC, and this method was not inferior to plasmakinetic electrocautery during the perioperative period. However, TURBt with the blue laser may provide the benefit to reduce preoperative blood loss and accelerate postoperative wound healing. Moreover, longer follow-up to confirm recurrence-free survival benefit was required.